2016
DOI: 10.1051/0004-6361/201628490
|View full text |Cite
|
Sign up to set email alerts
|

The cause of spatial structure in solar He i 1083 nm multiplet images

Abstract: Context. The He i 1083 nm is a powerful diagnostic for inferring properties of the upper solar chromosphere, in particular for the magnetic field. The basic formation of the line in one-dimensional models is well understood, but the influence of the complex threedimensional structure of the chromosphere and corona has however never been investigated. This structure must play an essential role because images taken in He i 1083 nm show structures with widths down to 100 km. Aims. To understand the effect of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…The commonly accepted line formation mechanism for He i D 3 and He i 10830 Å in the upper chromosphere is through photoionization-recombination (Goldberg 1939;Zirin 1975;Mauas et al 2005;Andretta et al 2008;Centeno et al 2008;Leenaarts et al 2016). The neutral helium triplet levels are populated by incoming EUV radiation from the corona and transition region to the upper chromosphere, resulting in absorption lines formed by scattering of continuum photons.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly accepted line formation mechanism for He i D 3 and He i 10830 Å in the upper chromosphere is through photoionization-recombination (Goldberg 1939;Zirin 1975;Mauas et al 2005;Andretta et al 2008;Centeno et al 2008;Leenaarts et al 2016). The neutral helium triplet levels are populated by incoming EUV radiation from the corona and transition region to the upper chromosphere, resulting in absorption lines formed by scattering of continuum photons.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling the the radiation in 1D would expose such a structure to EUV radiation only from the top which would result in a lower photoionization rate and fewer ions. An example of this is given in Figure 7 of Leenaarts et al (2016) where a comparison between 1D and 3D radiative transfer shows that an exposed chromospheric structure has a higher number density of He ii in the 3D case than in the 1D case.…”
Section: Discussionmentioning
confidence: 99%
“…Later he also found that the PR mechanism can not be the primary formation mechanism of He ii λ304 in quiet regions (Andretta et al 2003). The subordinate helium lines, however, have been shown to be sensitive to coronal illumination (Wahlstrom & Carlsson 1994;Avrett et al 1994;Andretta & Jones 1997;Mauas et al 2005;Centeno et al 2008;Leenaarts et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bifrost solves the equations of resistive MHD, together with non-LTE radiative losses in the photosphere and chromosphere, optically thin losses in the corona, and heat conduction along field lines. We used a snapshot from the "cb24bihe-halfxy-100" run, which was also used in Leenaarts et al (2016) and Golding et al (2017). The simulation box spans from the upper convection zone up to the lower corona, with an horizontal extent of 24×24 Mm and a vertical extent of 16.8Mm, from 2.5Mm below the photosphere to 14.3Mm above it.…”
Section: Bifrost Modelmentioning
confidence: 99%